Plasma patches inside the polar cap and auroral oval: the impact on the spaceborne GPS receiver - Xiong Chao (Journal of Space Weather and Space Climate, 2019)
In this study, we focus on plasma patches with very dense plasma in the southern hemisphere during the main phase of 2015 St. Patrick’s Day storm. With in situ electron densities exceeding 1.5 × 1012 m−3 at 450–500 km altitude, the patches cause strong signal outages of the global positioning system (GPS) receivers on board Swarm satellites. By using the field-aligned currents derived from the Swarm magnetic measurements, we determined whether the satellites fly inside the auroral oval or not. Different influences on the spaceborne GPS receiver are seen when these patches are located at different latitude regions, e.g., inside the polar cap or auroral oval. The simultaneously measurements of 2 Hz electron density as well as 50 Hz magnetic signatures from Swarm show that when large-scale polar cap patches transported from dayside lower latitude entering the cusp region, irregularities with much finer scale-size are generated; associated with various instabilities inside the cusp region, the small-scale irregularities cause much more severe influence on the GPS signals. This is the first direct evidence to show that when plasma patches are located inside the cusp region, the spaceborne receiver experiences stronger outage of GPS signals.